Survival of children with rare structural congenital anomalies: a multi-registry cohort study - Sue Jordan (Orphanet Journal of Rare Diseases, 2022)
BackgroundCongenital anomalies are the leading cause of perinatal, neonatal and infant mortality in developed countries. Large long-term follow-up studies investigating survival beyond the first year of life in children with rare congenital anomalies are costly and sufficiently large standardized cohorts are difficult to obtain due to the rarity of some anomalies. This study aimed to investigate the survival up to 10 years of age of children born with a rare structural congenital anomaly in the period 1995–2014 in Western Europe.MethodsLive births from thirteen EUROCAT (European network for the epidemiological surveillance of congenital anomalies) population-based registries were linked to mortality records. Survival for 12,685 live births with one of the 31 investigated rare structural congenital anomalies (CAs) was estimated at 1 week, 4 weeks and 1, 5 and 10 years of age within each registry and combined across Europe using random effects meta-analyses. Differences between registries were evaluated for the eight rare CAs with at least 500 live births.ResultsAmongst the investigated CAs, arhinencephaly/holoprosencephaly had the lowest survival at all ages (58.1%, 95% Confidence Interval (CI): 44.3–76.2% at 1 week; 47.4%, CI: 36.4–61.6% at 1 year; 35.6%, CI: 22.2–56.9% at 10 years). Overall, children with rare CAs of the digestive system had the highest survival (> 95% at 1 week, > 84% at 10 years). Most deaths occurred within the first four weeks of life, resulting in a 10-year survival conditional on surviving 4 weeks of over 95% for 17 out of 31 rare CAs. A moderate variability in survival between participating registries was observed for the eight selected rare CAs.ConclusionsPooling standardised data across 13 European CA registries and the linkage to mortality data enabled reliable survival estimates to be obtained at five ages up to ten years. Such estimates are useful for clinical practice and parental counselling.